Emotion and the Law : Psychological Perspectives - Bornstein, Brian H. (Springer, 2017)
1. Emotion and the Law: A Field Whose Time Has Come. 2. Affect in Legal and Forensic Settings: The Cognitive Benefits of Not Being Too Happy. 3. Emotional Influences on Judgments of Legal Blame: Whether They Should, and What to Do About It. 4. Explorations in Juror Emotion and Juror Judgment...